Manual of fast track recovery for colorectal surgery - Kennedy, Robin H.; Ljungqvist, Olle; Mythen, Monty G. (Enhanced Recovery, 2012)
Manual of Fast Track Recovery for Colorectal Surgery provides a broad overview on enhanced recovery, with expert opinions from leaders in the field regarding elements of enhanced recovery care that are generic and specific to colorectal surgery. This book covers the patient journey through such a programme, commencing with optimisation of the patient's condition, patient education and conditioning of their expectations. Manual of Fast Track Recovery for Colorectal Surgery investigates the metabolic response to surgery, anaesthetic contributions and optimal fluid management, after surgery. It also details examples of enhanced recovery pathways and  practical tips on post-operative pain control, feeding, mobilisation and criteria for discharge. Manual of Fast Track Recovery for Colorectal Surgery is a valuable reference tool for colorectal surgeons, anaesthetists, ward nurses and other members of the team involved in perioperative care: pain control specialists, physiotherapists, dietitians, specialist therapists (such as colorectal and stoma nurses), and outpatient nurses.